The The Effectiveness of the Indonesian Government's Strategy in Internationalising the Indonesian Language - Aulia, Chisty; Argenti, Gili; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
The internationalisation of the Indonesian language has emerged as a strategic priority within Indonesia’s agenda for linguistic and cultural diplomacy. Underpinned by robust historical, legal, and linguistic foundations, Indonesian language is increasingly recognised for its potential to serve as an international language. This study aims to assess the effectiveness of government strategies in advancing this objective, focusing on regulatory policies, educational programmes, cultural diplomacy, and the utilisation of media and technology. Employing a descriptive qualitative method, the research relies on secondary data gathered through literature review and documentation, which are analysed through data reduction, presentation, and conclusion drawing. The findings indicate that although notable progress has been made in promoting the global presence of Indonesian language, challenges remain concerning coordination, budgetary support, and resource development. The designation of Indonesian language as the tenth official language at the UNESCO General Conference represents a significant milestone. Nevertheless, sustained multi-stakeholder collaboration and policy reinforcement are essential. With consistent strategies and effective synergy, Indonesian language holds substantial potential as a soft power instrument, enhancing Indonesia’s global identity and diplomatic engagement.